THE INFLUENCE OF ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE AT BANDUNG CITY HOSPITAL - Jiwa Riwayanti (STIA Bagasasi, 2023)
In the current era of industrialization, the hospital is a form of organization engaged in health services. One of the efforts made is to support referrals from basic level services, such as puskesmas. For this reason, the puskesmas is a referral center for basic level health services. Changes that occur in today's society greatly affect this competition, both changes in demography, socio-economics, science and technology, market competition and human resources. One of the factors for decreasing employee performance is thought to be organizational culture. Problems related to organizational culture at Muhammadiyah Bandung Hospital are the habit of lateness of employees, the habit of lateness of employees coming to work after rest hours, the habit of employees waiting for orders from superiors in carrying out tasks and the habits of employees not being on time in carrying out tasks. Therefore this study aims to determine the influence of organizational culture on employee performance. The method used in this study is in accordance with the expected objectives, namely descriptive and verification methods. Organizational culture (X) as the independent variable and employee performance as the dependent variable (Y). The population in this study were all employees at the Muhammadiyah Bandung Hospital. The sample specified in this study amounted to 50 respondents. The data collection used is through literature study, field study (interviews, questionnaires, and observations) with descriptive analysis and quantitative analysis. Data processing was carried out by validation and reliability tests using SPSS. The results of the study state that there is a fairly strong relationship between organizational culture and employee performance, and there is a positive influence between organizational culture on employee performance at Bandung Hospital.